Complete Posterior Sagittal Anorectal Mobilization (PSAM): A new surgical approach for pediatric pelvic‐perineal tumor resections. Issue 8 (1st May 2018) - Martucciello, Giuseppe; Pio, Luca; Avanzini, Stefano; Garaventa, Alberto
Abstract : Introduction: Diffuse or massive tumors involving the perineal and pelvic compartments may require aggressive surgical treatment in children. The authors, propose and present their results using a Posterior Sagittal Anorectal Mobilization (PSAM) Methods: The oncologic patient is placed in a prone position with the pelvis elevated, without a previous colostomy. A 10 Ch bladder catheter is positioned. A midline sagittal incision is performed from the coccyx to the posterior margin of the anus. Fine electrocautery is used to obtain an accurate dissection all around the anal margin itself. The incisional so involves the midline dissection into the perineal body. Reconstruction is achieved by the classical pelvic‐perineal anatomical structure approximation. Results: The authors describe for the first time a novel posterior anorectal mobilization technique for four children with pelvic‐perineal tumors. No intraoperative or post‐operative complications occurred. The oldest boy presented at follow‐up a complete normal faecal and urinary continence (Krickenbeck criteria). Conclusion: The presented technical approach, defined as PSAM, is completely suitable for surgical resection of perineal‐pelvic tumors, without the need of more invasive operations including transpubic dissection and/or anorectal split. Moreover, nervous and muscular sphincter structures are easily identified and preserved.